Is nucleate cell count and neutrophil to lymphocyte ratio related to patients with audiographically distinct sudden sensorineural hearing loss?. Issue 20 (May 2018) - Sun, Yuanyuan; Xia, Liang; Wang, Hui; Chen, Zhengnong; Wu, Yaqin; Chen, Bin; Shi, Haibo; Feng, Yanmei; Yin, Shankai
Abstract : Abstract: The aim of this study was to investigate the possible relationships between sudden sensorineural hearing loss (SSNHL) patients with distinct audiographic data and nucleate cell count and neutrophil to lymphocyte ratio (NLR). SSNHL patients differed in audiographic curves were included, 40 with low-frequency SSNHL (LF-SSNHL), 33 with high-frequency SSNHL (HF-SSNHL), 36 with all-frequency SSNHL (AF-SSNHL), 34 with total-deafness SSNHL (TD-SSNHL), and 31 age- and sex-matched healthy controls. Peripheral venous blood samples were collected and nucleate cell such as white blood cell (WBC), neutrophil and lymphocyte, and NLR were measured. Each group was divided into recovery and unrecovery subgroup according to hearing levels after 1-month therapy, and then compared the difference of the count of WBC, neutrophil and lymphocyte, and NLR between the 2 subgroups. The WBC count of the HF-SSNHL, AF-SSNHL, and TD-SSNHL group was significantly higher than that of the control group ( P = .024, P = .003, P = .008, respectively), not for LF-SSNHL group ( P = .248). WBC count between LF-SSNHL and AF-SSNHL group was significantly different ( P = .045). The neutrophil count of the HF-SSNHL, AF-SSNHL, and TD-SSNHL group was significantly higher than that of the control group ( P = .002, P = .000, P = .000, respectively), not for LF-SSNHL group ( P = .069). Neutrophil count of LF-SSNHL was significantly lower than that of AF-SSNHL and TD-SSNHL groups ( P = .014, P = .013). The lymphocyte count of AF-SSNHL and TD-SSNHL group was significantly lower than that of the control group ( P = .027, P = .003), not for LF-SSNHL and HF-SSNHL group ( P = .119, P = .054). NLR of HF-SSNHL, AF-SSNHL, and TD-SSNHL group was significantly higher than that of the control group ( P = .001, P = .000, P = .000, respectively), not for LF-SSNHL group ( P = .070). NLR of LF-SSNHL was significantly lower than that of AF-SSNHL and TD-SSNHL group ( P = .041, P = .005). In HF-SSNHL patients, lymphocyte count of unrecovery subgroup was significantly lower, while NLR of the unrecovery subgroup were significantly higher than those of recovery subgroup ( P = .017, P = .015). The count of WBC, neutrophil, lymphocyte, and NLR may be related to SSNHL, but they were unreliable at predicting SSNHL characterized by differences in audiometric curves. Higher NLR and lower lymphocyte count maybe used to evaluate prognosis of HF-SSNHL patients.